The Nexus Between Remittances, Natural Resources, Economic Growth, Healthcare and Environmental Sustainability In CIS Countries - Kuziboev, Bekhzod; Zografou, Zoi; Saidmamatov, Olimjon; Chupanov, Sanat (International Journal of Energy Economics and Policy, 2024)
Globally, the issues about sustainable development are on the increase, especially in emerging economies as CIS countries. Due to rising migration and remittances, natural resources are degraded, and economic expansion might pose serious challenges to the environment and healthcare. Thus, this research looks at how life expectancy is affected by economic growth, natural resources and carbon dioxide (CO2) emissions in 11 CIS countries (Armenia, Azerbaijan, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia, Tajikistan, Ukraine, and Uzbekistan) by con-trolling energy consumption from 1990 to 2019. The Dumitrescu-Hurlin causality test discloses a cointegration between life expectancy, remittances, natural resources, economic growth, and CO2 Emissions. The empirical analysis indicates that life expectancy is positively correlated with re-mittances and GDP while water withdrawal and CO2 emissions have negative impact on life ex-pectancy in the case of CIS countries. Our empirical findings may provide insightful policy implications towards strengthening the public healthcare system. Therefore, appropriate policy responses can be developed towards advanced public healthcare and environmentally sustainable sources of energy in order to achieve the sustainable development goals.